Effect of Implicit Learning Methods With the External Focus of Attention on Bowling Skills in Children With Autism Spectrum Disorder: A Randomized Control Trial Study - Mina Khodayari; Rasoul Yaali; Farhad Ghadiri (Brain and Behavior)
ABSTRACT Purpose The aim of the current study was to compare implicit learning methods with an emphasis on the external focus of attention on bowling skill in autistic children. Method Twenty children with autism spectrum disorder (ASD) were selected. After the participants were randomly divided into two groups, the pretest was performed, evaluating the participants both quantitatively (score of bowling pins falling) and qualitatively (TGMD3 subscale test of underhand ball throwing). Group A was trained using the errorless learning method with the external focus of attention, while Group B was trained using the analogical learning method with the external focus of attention. Findings The results showed that analogical learning with the external focus of attention has significant effects (p ≤ 0.05) on both bowling and underhand ball‐throwing skills in autistic children. Errorless learning with external focus of attention, on the other hand, had a significant effect (p ≤ 0.05) on the bowling skill. Conclusion The results of the research showed that analogical learning with an external focus of attention can be effective in developing both bowling skill and underhand ball‐throwing skill in children with ASD; however, errorless learning with an external focus of attention was useful in developing bowling skill and failed to show a significant effect on enhancing the underhand ball‐throwing skill in children diagnosed with ASD. Trial Registration IRCT20220920056007N1.